The Quebec Observatory on End-of-Life Care for People with Dementia: Implementation and Preliminary Findings. Issue 4 (9th December 2022) - Bravo, Gina; Arcand, Marcel; Wilchesky, Machelle; Verreault, René; Bilodeau, Charles; Trottier, Lise
Abstract: Most Canadians with dementia die in long-term care (LTC) facilities. No data are routinely collected in Canada on the quality of end-of-life care provided to this vulnerable population, leading to significant knowledge gaps. The Quebec Observatory on End-of-Life Care for People with Dementia was created to address these gaps. The Observatory is a research infrastructure designed to support the collection of data needed to better understand, and subsequently enhance, care quality for residents dying with dementia. This article reports on the main steps involved in setting up the Observatory, as well as a pilot study that involved 172 residents with dementia who died between 2016 and 2018 in one of 13 participating facilities. It describes the data gathered, methodological changes that were made along the way, feedback from participating facilities, and future developments of the Observatory.